2017
DOI: 10.1007/s12274-017-1694-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon lithography for 3D magnetic nanostructure fabrication

Abstract: Ferromagnetic materials have been utilized as recording media in data storage devices for many decades. The confinement of a material to a two-dimensional plane is a significant bottleneck in achieving ultra-high recording densities, and this has led to the proposition of three-dimensional (3D) racetrack memories that utilize domain wall propagation along the nanowires. However, the fabrication of 3D magnetic nanostructures of complex geometries is highly challenging and is not easily achieved with standard li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 28 publications
0
85
1
Order By: Relevance
“…The fabrication method of such 3D interlinked nanostructures is based on porous alumina membranes filled via electrochemical deposition, which constitutes a low‐cost method, is highly tunable, with no need of vacuum or atmosphere‐controlled environment, and is easily scalable to the industry. Other methods of obtaining 3D nanostructures are ion‐track‐etched polymeric membranes (however, by this technique, certain parameters cannot be controlled, such as the exact number and position of interconnections between NWs), two‐photon lithography, or focused electron beam‐induced deposition (which are comparably much more expensive and time‐consuming). Nevertheless, these methods have the advantage of being able to produce more complex 3D structures of virtually any magnetic material.…”
mentioning
confidence: 97%
“…The fabrication method of such 3D interlinked nanostructures is based on porous alumina membranes filled via electrochemical deposition, which constitutes a low‐cost method, is highly tunable, with no need of vacuum or atmosphere‐controlled environment, and is easily scalable to the industry. Other methods of obtaining 3D nanostructures are ion‐track‐etched polymeric membranes (however, by this technique, certain parameters cannot be controlled, such as the exact number and position of interconnections between NWs), two‐photon lithography, or focused electron beam‐induced deposition (which are comparably much more expensive and time‐consuming). Nevertheless, these methods have the advantage of being able to produce more complex 3D structures of virtually any magnetic material.…”
mentioning
confidence: 97%
“…The 3DNL arrays have dimensions 50µm × 50µm × 10µm (Fig 2a). [41]. Some methodologies allow this to be optimised (see discussion) but in this study, since evaporation simply coats the top surface of the polymer nanowire, it is not a concern.…”
Section: Resultsmentioning
confidence: 98%
“…This methodology is very exciting but has not been applied to the manufacture of complex 3D nanostructured lattices. Finally, two-photon lithography and electrodeposition has been used to fabricate complex 3D magnetic nanostructures [41,42] which were also very pure (>95% Co). Unfortunately, the structures made within this study were relatively large (>400nm) and shown to be multi-domain [41].…”
mentioning
confidence: 99%
“…In this paper, a micro-scale fracture specimen was fabricated by 2PP-DLW [11][12], followed by Ni electrodeposition. Fig.…”
Section: Specimen Preparation and Fabricationmentioning
confidence: 99%